2016
DOI: 10.1142/s1793005716500101
|View full text |Cite
|
Sign up to set email alerts
|

Certain Metrics in m-Polar Fuzzy Graphs

Abstract: In this paper, we present certain metrics in m-polar fuzzy graphs including antipodal m-polar fuzzy graphs and self median m-polar fuzzy graph of given m-polar fuzzy graphs. We illustrate the concepts of metric in m-polar fuzzy graphs by several examples and investigate some of their properties. We discuss some properties of isomorphic m-polar fuzzy graphs. We also describe an application of m-polar fuzzy graph in a road network. 135 New Math. and Nat. Computation 2016.12:135-155. Downloaded from www.worldscie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Our research is also partially motivated by some articles regarding fuzzy mathematical objects [2][3][4][5]. Furthermore, if one is interested in other variants of metrics for graphs, he could consult either [6] or [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our research is also partially motivated by some articles regarding fuzzy mathematical objects [2][3][4][5]. Furthermore, if one is interested in other variants of metrics for graphs, he could consult either [6] or [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Chen et al [20] introduced the idea of m-polar fuzzy sets, as an extension of bipolar fuzzy sets and showed that bipolar fuzzy sets and 2-polar fuzzy sets are cryptomorphic mathematical notions and that we can obtain concisely one from the corresponding one [20]. Recently, Akram with others applied the concept of m-polar fuzzy sets in different directions, like, Lie algebras [21,22], graph theory [23,24], groups [25], lattices [26] and matroids [27]. Akrem published a book on m-polar fuzzy graphs [28], in which he provided several types of m-polar fuzzy graphs with applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since most of the mathematical models can be formalized or represented via vertices and edges, studying the properties of the distances between any two graphs becomes a vital approach to explore the intrinsic properties of a mathematical structure or a real mathematical object [1,2], even being used on some fuzzy objects [3,4]. Some ingenious metrics for handling these fuzzy objects have been explored in depth [5,6]. In this article, we put forward two metrics for graphs with labelled vertices and unlabelled vertices, respectively.…”
Section: Introductionmentioning
confidence: 99%